The rise of Talmud - Vidas, Moulie (Bible and the humanities, 2025)
"The rabbinic sages of late antiquity are known for their sophisticated and creative reading of Scripture, but rabbinic literature also includes elaborate commentary on another kind of texts: the sages' own teachings. This book argues that the development of this commentary, later called Talmud, transformed the sages' self-perception and intellectual world. By studying the first collection of commentary on rabbinic teachings, the often neglected and difficult Talmud Yerushalmi, and comparing it with earlier rabbinic texts, this study shows how ancient Talmudic scholars presented a new understanding of these teachings: they saw them as the products of individual sages and as resulting from problem-fraught processes of composition and transmission"--